IMMU-02. CHIMERIC ANTIGEN RECEPTOR (CAR) T CELL NEUROTOXICITY CORRELATES WITH PRETREATMENT AND ACUTE CSF NEUROFILAMENT LIGHT CHAIN (NFL) LEVELS. (4th December 2020) - Gust, Juliane; Wilson, Ashley; Finney, Olivia; Hartsuyker, Kendra Jae; Narayanaswamy, Prabha; Wu, Vicky; Garden, Gwenn; Annesley, Colleen; Gardner, Rebecca
Abstract: OBJECTIVE: Immunotherapy for hematologic malignancies with CD19-directed CAR T cells is complicated by neurotoxicity in approximately 40% of patients. We have previously reported evidence of glial injury in pediatric patients with CAR T neurotoxicity by elevated CSF levels of GFAP and S100b. We now hypothesize that NFL is also a useful biomarker of neuronal injury related to abnormal blood-brain-barrier and glial function. METHODS: We used the Mesoscale Discovery platform to measure CSF and serum NFL levels in a consecutive cohort of 43 pediatric patients with B cell ALL who received CD19-directed CAR T cells. In addition, we will present expansion cohort measurements of NFL and GFAP (N=95). RESULTS: CSF NFL levels prior to CAR T cell infusion positively correlated with the risk of subsequently developing severe neurotoxicity (no neurotoxicity, median 275pg/mL, mild 378pg/mL, severe 951pg/mL, P=0.0182 for severe vs none, P=0.0458 for severe vs mild). During neurotoxicity, mean CSF NFL levels increased to 1179pg/mL (mild neurotoxicity, P=0.0338) and 1345 pg/mL (severe neurotoxicity, P=0.0148), respectively. In serum, pretreatment NFL levels were highly abnormal in many patients (median 368pg/mL, range 10–56, 321pg/mL; healthy control median 4pg/mL, range 1–7.5pg/mL). However, there was no correlation with neurotoxicity, history of CNS radiation, peripheral neuropathy, stem cell transplant, or number of prior chemotherapies. Day 7 serum NFL levels did not change significantly (median 439pg/mL, range 5–17, 439pg/mL, P=0.3254). CONCLUSION: We conclude that CSF NFL is promising biomarker of CAR T neurotoxicity risk and severity. The abnormal baseline serum NFL concentrations remain unexplained and require further study.